2013
DOI: 10.1007/s00894-013-1918-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of hydrogen storage capacity of few-layer graphene

Abstract: The adsorption of molecular hydrogen on few-layer graphene (FLG) structures is studied using molecular dynamics simulations. The interaction between graphene and hydrogen molecules is described by the Lennard-Jones potential. The effects of pressure, temperature, number of layers in a FLG, and FLG interlayer spacing are evaluated in terms of molecular trajectories, binding energy, binding force, and gravimetric hydrogen storage capacity (HSC). The simulation results show that the effects of temperature and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Atomic/molecular simulation avoids experimental noise and can be used to analyze atomic/molecular trajectories and thermodynamic properties. Many nanosystems have been analyzed using MD, such as nanoimprinting, 9,10 metallic NWs under torsion, 11,12 hydrogen storage capacity of graphene, 13,14 and dip-pen nanolithography. 15, 16 Pereira and da Silva 17 modeled the cold welding of Au-Au, Ag-Ag, and Au-Ag NWs with diameters of 4.3 nm at a temperature of 300 K. They found that defective NWs can reconstruct their face-centered cubic (fcc) structure during the welding process.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic/molecular simulation avoids experimental noise and can be used to analyze atomic/molecular trajectories and thermodynamic properties. Many nanosystems have been analyzed using MD, such as nanoimprinting, 9,10 metallic NWs under torsion, 11,12 hydrogen storage capacity of graphene, 13,14 and dip-pen nanolithography. 15, 16 Pereira and da Silva 17 modeled the cold welding of Au-Au, Ag-Ag, and Au-Ag NWs with diameters of 4.3 nm at a temperature of 300 K. They found that defective NWs can reconstruct their face-centered cubic (fcc) structure during the welding process.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, often the Lennard-Jones (LJ) potential is used. 20,21 However, the deficiencies of the LJ scheme at both the short and long ranges are well known. [22][23][24] Beyond this model, Pirani et al proposed an Improved Lennard-Jones (ILJ) potential, 22,23 simple and accurate, which offers greater flexibility by adding an extra parameter in such a way that it eliminates most of the shortcomings of the LJ model.…”
Section: Introductionmentioning
confidence: 99%
“…2f. The efficiency of hydrogen storage for a graphene bubble structure can be improved by suitably adjusting the graphene interlayer spacing [33]. This article does not provide an exhaustive description in this regard.…”
Section: Effect Of Number Of Graphene Layersmentioning
confidence: 98%